2006
DOI: 10.1016/j.amjhyper.2005.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Association Study Between C-Reactive Protein Genes and Ischemic Stroke in Japanese Subjects

Abstract: The rs1800947 SNP and the C-C-C haplotype in the CRP gene appear to be prognostic markers of ischemic stroke and this polymorphism could be a useful genetic marker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 29 publications
1
45
0
Order By: Relevance
“…In acute-phase reactions, CRP concentrations can increase up to a thousand times, and the association between elevated CRP concentrations and progression of atherosclerosis is well documented [28] . Current studies have found the 1059G/C polymorphism in exon 2 of the CRP gene to be an independent genetic risk factor for ischemic stroke [29] and atherosclerosis [30] in older Japanese individuals. However, the association of this variant with cerebrovascular events could not be replicated in younger Chinese subjects [31] , which suggests that the effect of the GC genotype might be associated with age.…”
Section: Ischemic Strokementioning
confidence: 99%
“…In acute-phase reactions, CRP concentrations can increase up to a thousand times, and the association between elevated CRP concentrations and progression of atherosclerosis is well documented [28] . Current studies have found the 1059G/C polymorphism in exon 2 of the CRP gene to be an independent genetic risk factor for ischemic stroke [29] and atherosclerosis [30] in older Japanese individuals. However, the association of this variant with cerebrovascular events could not be replicated in younger Chinese subjects [31] , which suggests that the effect of the GC genotype might be associated with age.…”
Section: Ischemic Strokementioning
confidence: 99%
“…However, since this control group was a supercontrol that was comprised of older people who did not have any diseases, this was not considered to have caused any bias in our analyses. [25][26][27] Results Table 1 shows the clinical features of the CI patients and control subjects. Significant differences in the systolic blood pressure (SBP), diastolic blood pressure (DBP), pulse, creatinine, total cholesterol, hyperlipidemia, diabetes and smoking were observed between the CI and control groups.…”
Section: Discussionmentioning
confidence: 99%
“…Although these supercontrol groups have higher ages than the case groups being studied, it has been shown that these groups are acceptable for use in case-control studies of late-onset diseases. 26 Table 2 shows the distribution of the genotypes and alleles of the five SNPs. The genotyping success rate in all SNPs was 100%.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, the use of the so-called "super control" has been widely accepted in case-control studies for common diseases that appear later in life. 18 Here, we used a "super control" group, as healthy elderly subjects have been found to be more suitable than young or middleaged subjects when determining phenotypes of cardiovascular diseases related to aging. MI is an age-influenced disease, and therefore a "super control" group rather than an age-matched control group is better in this type of experiments with regard to increasing the statistical power.…”
Section: Discussionmentioning
confidence: 99%